Az alkalmazott szociálgeográfia lehetőségei a turizmus kutatásában – Budapest I. kerülete példáján - Michalkó, Gábor (Tér és Társadalom, 1996)
The study introduces the recently acquired methodological and theoretical results of the research project entitled "Social Geographical Survey of Tourism in Budapest". Using one of the most frequented part of the city, i. e. District I, the study reveals those specific features of the local society, foreign visitors, services and the self-government that influence the touristic activity of this urban quarter on the one hand and the conflicts among the above factors and the development of tourism on the other hand. During the research special attention was paid to practical aspects and the scientific grounding of the regional development plans. When compared to the domestic studies on urban tourism, this piece of work has fewer economic aspects and concentrates on the human factors related to functions rather. During data collection questionnaires, detailed interviews and non-published information was used. In the course of data evaluation the Buda Castle, part of the World Heritage and its surroundings were found to demand general, qualitative development based on subtle regional potentials in the future in order to have an absolute international attraction in themselves. In doing so the interests of the local population have to be observed as much as that of the expectations and touristic customs of the foreign visitors.